2021
DOI: 10.1111/imr.12962
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of host cell mitochondrial activity as Mycobacterium leprae’s strategy to evade host innate immunity

Abstract: This article is part a series of reviews covering Immunity to Mycobacteria appearing in Volume 301 of Immunological Reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 156 publications
(328 reference statements)
2
22
0
1
Order By: Relevance
“…Similar to M.tb, M.leprae upregulates lipid uptake and biosynthetic pathways in infected macrophages, particularly cholesterol (88,89). Mechanistically, infection with M.leprae increases macrophage expression of scavenger receptor (SR)A-I and CD36, promoting the foamy macrophage phenotype (90,91).…”
Section: Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to M.tb, M.leprae upregulates lipid uptake and biosynthetic pathways in infected macrophages, particularly cholesterol (88,89). Mechanistically, infection with M.leprae increases macrophage expression of scavenger receptor (SR)A-I and CD36, promoting the foamy macrophage phenotype (90,91).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Notably, M.leprae infection reduces host cell mitochondrial activity in a distinctive manner (88). Oliveira et al proposed that cytosolic accumulation of lipids in M.leprae-infected macrophages may contribute to mitochondrial shutdown and suppression of their innate immune functions (88).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Most individuals develop an efficient immune response to M. leprae after exposure. However, in a small number of exposed individuals, the infection may not be controlled at the mucosal sites, favoring M. leprae growth in the host cells and spreading ( Lázaro et al, 2010 ; Oliveira et al, 2021 ). Following an increase in the bacillary load, the pathogen may disseminate via bloodstream to other body parts.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the evolutionary strategy that involved the reduction in its genome to a minimal set of genes, M. leprae became dependent on the host cell metabolism, making it highly susceptible to host-target strategies such as the inhibition of cholesterol synthesis by statins, for example ( Cole et al, 2001 ; Mattos et al, 2011b ; Lobato et al, 2014 ). Medeiros et al also demonstrated that after infection, M. leprae modulates Schwann cell metabolism to a more glycolytic profile, with increased glucose uptake and consumption followed by a reduction in oxidative phosphorylation, which results in mitophagy induction ( Oliveira et al, 2021 ). All these host cell metabolic changes are crucial to the lipid accumulation and foamy aspect of infected cells, a hallmark that is crucial to M. leprae infection success.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies revealed that the antioxidant defense network alleviates oxidative stress, regulates inflammatory responses, and improves immunity by ensuring redox balance and adaptive homeostasis (21)(22)(23). The rapid development of sequencing technology offers more possibilities for identifying more valuable tumor markers (24,25).…”
Section: Introductionmentioning
confidence: 99%